Guide to the national parks of the United States. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 2012)
Offers descriptions, road maps, itineraries, travel tips, costs, and contact information for national parks ranging from Virginia's Shenandoah to Alaska's Glacier Bay.
Includes index.
Keywords: National parks and reserves -- United States -- Guidebooks; National parks and reserves -- United States; United States -- Guidebooks; United States -- Guidebooks; Travel guides